Gambaran Penyakit Demam Berdarah Dengue (DBD) di Dusun Singkil, Giring, Paliyan, Gunungkidul, Yogyakarta - Aliya Nugrafitra Murti; Miftazana Firdaus Rizki Putri; Galuh Intan Novitasari; Aulia Nur Aini; Salsabila Giska Indraswari; Narto Narto; Tri Mulyaningsih (JPS : Jurnal Pengabdian Serulingmas, 2022)
Indonesia's health development is in the phase of re-emerging diseases. One such case is Dengue Hemorrhagic Fever (DBD), a disease transmitted by the Aedes sp. infected with the dengue virus. Based on data from the Health Office of the Special Region of Yogyakarta, the most cases of dengue fever were in Gunungkidul Regency, namely 333 patients and 2 people died. Singkil located in Giring Village, Paliyan District, is one of the hamlets in Gunungkidul that has dengue cases. Students of the D3 Sanitation study program at the Environmental Health Department of the Health Polytechnic of the Ministry of Health Yogyakarta conducted a Community Field Work Practice with several activities related to surveys, analysis, problem solving planning, socialization, and implementation of interventions regarding DHF, which aimed to reduce the transmission of DHF in the village. This activity will be held on January 3-29, 2022. The method of implementation is in the form of hands-on practice, and interviews. The data that has been obtained is processed and analyzed descriptively to describe the case. PSN activities are carried out at residents' homes. Based on the fieldwork practice, it was concluded that from making a problem map, there were 4 cases of dengue fever in 2021 and 1 case of dengue fever in 2022. The results obtained were 11 residents' houses that were positive for mosquito larvae. The provision of abate and medicinal plants was also carried out to prevent the occurrence of dengue fever.